2018
DOI: 10.1097/brs.0000000000002621
|View full text |Cite
|
Sign up to set email alerts
|

Flexion-Relaxation Phenomenon in Children and Adolescents With and Without Nonspecific Chronic Low Back Pain

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The physical examination and study interventions were delivered by a clinician with 20 years of experience. The sample size calculation was based on the mean value of the root mean square (RMS) for the multifidus muscle in flexion [ 22 ]. With an α risk of 0.05, a power of 0.8 and effect size of 0.3, a total of 33 individuals in each group was needed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical examination and study interventions were delivered by a clinician with 20 years of experience. The sample size calculation was based on the mean value of the root mean square (RMS) for the multifidus muscle in flexion [ 22 ]. With an α risk of 0.05, a power of 0.8 and effect size of 0.3, a total of 33 individuals in each group was needed.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, subjects with LBP tend to show significantly lower sEMG activity during the extension phase, suggesting that it might reflect neuromuscular abnormalities [ 16 , 17 ]. Previous studies have shown that FRP measurements could be useful for assessment of recovery and efficiency of certain therapeutic procedures in patients with LBP [ 18 , 19 , 20 , 21 , 22 , 23 ]. Considering the possible changes in muscle activity in different phases of flexion and re-extension and the inability to use sEMG signal normalization in LBP patients compared to healthy subjects, there is a need to calculate the flexion relaxation ratio (FRR) [ 9 , 10 , 11 , 12 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%